Corruption in a non-corrupt country: what does corruption look like in Finland? - Kimpimäki, Minna (International journal of comparative and applied criminal justice, 2018)
Finland is usually considered a country where corruption is rare, and this impression is reinforced by the good results that it has achieved in Transparency International’s Corruption Perceptions Index (CPI). The present study describes and assesses Finnish bribery legislation, as well as a number of recent judgments handed down by Finnish courts. The legislation is quite fragmented, consisting of some nine sections in three different chapters of the Criminal Code. The bribery cases heard by the Supreme Court mainly deal with quite small-scale bribery, such as where a public official has accepted restaurant services, trips or other benefits from private companies. However, in the last few years, the courts have also had to consider some larger-scale instances of bribery, where persons working for Finnish companies have been suspected of bribing foreign public officials. The article also takes up match-fixing and election funding and their connections to bribery.